2021
DOI: 10.1016/j.jsxm.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 Pandemic on the Psychosexual Functions of Healthcare Workers

Abstract: Background A novel infection, COVID-19, emerged in China and soon became a global pandemic. Pandemic conditions have resulted in stress in the workplace and led to anxiety among healthcare workers (HCWs), having negative impacts on different aspects of their lives, including their sexual function. Aim To evaluate the changes in the anxiety status of HCWs during the COVID-19 pandemic and the impact of anxiety on their sexual functions. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Occupational anxiety may have an impact on physical and mental disorders [17]. Negative effects on anxiety levels of healthcare professionals were observed during the pandemic [8,9,[18][19][20]. Anxiety and worries negatively affect sexual functionality [21].…”
Section: Discussionmentioning
confidence: 99%
“…Occupational anxiety may have an impact on physical and mental disorders [17]. Negative effects on anxiety levels of healthcare professionals were observed during the pandemic [8,9,[18][19][20]. Anxiety and worries negatively affect sexual functionality [21].…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies are available in the literature investigating the influence of the COVID-19 pandemic on the sexual functions of healthcare workers (27)(28)(29)(30)(31)(32). In the cross-sectional study by Culha et al Conducted with 232 healthcare professionals fighting COVID-19 in pandemic hospitals, the authors have reported that during the pandemic, libido, duration of foreplay, co-itus frequency decreased, and positions of coitus have changed.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Eroglu et al Evaluating the changes in anxiety among healthcare workers during the pandemic and the effect of anxiety on sexual functions, the scores of IIEF-15 and State Anxiety Inventory-I (STAI-I) were compared at the beginning and the 6th month of the pandemic. The authors have reported that the COVID-19 pandemic negatively affected the sexual life of healthcare workers and sexual function decreased in both sexes, and anxiety severity significantly increased (31). In a systematic review by Bakr et al Evaluating the changes in erectile functions in healthy controls and health care providers during the pandemic, the COVID-19 pandemic was concluded to be related to increasing ED rates, anxiety and depression increased the severity of ED more particularly in health care providers (32).…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore uncertain as to whether COVID-19 triggered incident adverse mental health symptoms, exacerbated existing or preclinical mental health symptom burden, or whether poor mental health existed already among HCW and remained during the pandemic. 14 There are a small number of longitudinal studies among HCW reporting levels of, for example, anxiety 61 and psychological distress, 62 which reported that they increased within 6 months from the beginning of the pandemic. However, published longitudinal studies are rare and have a short duration of follow-up.…”
Section: Limitationsmentioning
confidence: 99%